Youth Service Provision and Coordination among Members of a Regional Human Trafficking Task Force - Vollinger, Lauren (Journal of interpersonal violence, 2022)
Trafficked youth have numerous needs that must be addressed to give them opportunities to rebuild their lives. Few organizations offer comprehensive services to meet all these needs, which forces survivors to seek out services from multiple organizations and puts them at risk for not receiving important services. This study highlights the needs of organizations in an interagency task force that serve trafficked youth to identify barriers and generate potential solutions to service provision challenges. We conducted a mixed-methods needs assessment by conducting interviews with 15 service providers belonging to a regional human trafficking task force, which revealed a need for more services for trafficked youth, particularly in criminal justice and gender-based violence organizations. Implications of these findings include a need for centralized referral processes and more prevention services, such as a youth drop-in center and educational interventions.